2014
DOI: 10.1107/s2053230x14019347
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and preliminary crystallographic analysis of poly(3-hydroxybutyrate) depolymerase fromBacillus thuringiensis

Abstract: Poly[(R)-3-hydroxybutyrate] (PHB) is a microbial biopolymer that has been commercialized as biodegradable plastics. The key enzyme for the degradation is PHB depolymerase (PhaZ). A new intracellular PhaZ from Bacillus thuringiensis (BtPhaZ) has been screened for potential applications in polymer biodegradation. Recombinant BtPhaZ was crystallized using 25% polyethylene glycol 3350, 0.2 M ammonium acetate, 0.1 M bis-tris pH 6.5 at 288 K. The crystals belonged to space group P1, with unit-cell parameters a = 42.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Most methods to identify new nPHB depolymerase is based on sequence comparison with already known depolymerase, either by comparing their phaZ genes in the other species, or phaC genes ( Tseng et al, 2006 ; Chen et al, 2009 ; Sznajder and Jendrossek, 2014 ), or through the blast search of the consensus motif. To date, only one PHB degradation enzyme (PhaZ) was well characterized in B. thuringiensis ( Tseng et al, 2006 ; Wang et al, 2014 ). Obtained results indicated that these methods all suffer from some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Most methods to identify new nPHB depolymerase is based on sequence comparison with already known depolymerase, either by comparing their phaZ genes in the other species, or phaC genes ( Tseng et al, 2006 ; Chen et al, 2009 ; Sznajder and Jendrossek, 2014 ), or through the blast search of the consensus motif. To date, only one PHB degradation enzyme (PhaZ) was well characterized in B. thuringiensis ( Tseng et al, 2006 ; Wang et al, 2014 ). Obtained results indicated that these methods all suffer from some limitations.…”
Section: Discussionmentioning
confidence: 99%